INTER-OBSERVER VARIABILITY IN HISTOPATHOLOGICAL INTERPRETATION OF GLIOMAS - Dr. Sabeen Nasir; Dr. Asif Ali; Dr. Ishaq Khan; Dr. Naveed Sharif (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Inter-observer variability complicates histopathological diagnosis in gliomas, especially in distinguishing grades and tumor types using morphology alone. This study aimed to quantify agreement between two consultant pathologists using WHO 2021 criteria via Kappa and ICC analysis. Methods: A total of 128 glioma biopsy specimens were independently assessed by two consultants for diagnosis and grading under WHO 2021 classification. Discrepancies were categorized as agreement, minor disagreement (within-grade differences), or major disagreement (cross-grade or tumor-type difference). Inter-observer reproducibility was evaluated using Kappa statistics and ICC. Results: Complete agreement occurred in 42/128 cases (32.8%), with disagreement in 86 (67.2%), including 58 major and 28 minor conflicts. The Kappa coefficient was 0.383 (fair agreement), and ICC was 0.51 (moderate reliability). Conclusions: Significant inter-observer variability persists in glioma histopathology when relying solely on morphology. Integrated molecular classification (WHO 2021) and adjunctive tools may enhance diagnostic consensus and reduce subjectivity.